Recognizing Tumor Origin for Lymphoid Tumor of Unknown Primary via Total-Body PET/CT Scan—Case Report - Lu, Weizhao; Qiu, Jianfeng; Xie, Xue; Li, Kun; Duan, Yanhua; Li, Min; Ma, Chao; Cheng, Zhaoping; Liu, Sijin (Frontiers in Oncology, 2022)
Localizing the site of tumor origin for patients with lymphoid tumor is fairly difficult before the definitive detection of the primary tumor, which causes redundant imaging examinations and medical costs. To circumvent this obstacle, the emergence of the world’s first total-body positron emission tomography/computed tomography (PET/CT) provides a transformative platform for simultaneously static and dynamic human molecular imaging. Here, we reported a case of lymph node metastasis from an unknown primary tumor, and the primary tumor was detected with the aid of the total-body PET/CT scanner. This patient with right neck mass was subjected to static and dynamic PET scan, as the static PET imaging found irregular thickening of the upper rectal wall and the dynamic PET imaging recognized the associations between the lymph metastasis and the rectal tumor lesions. The diagnosis by the total-body PET/CT was confirmed by pathological examination.